FASILITASI BAKTI SOSIAL MAHASISWA UNTUK MASYARAKAT PESISIR YANG TERPENCIL DI WILAYAH KABUPATEN KARAWANG - Nopiana, Medi; Ramdani, Danny; Chaerudin, Chaerudin; Dailibas, Dailibas; Suherman, Achmad (Madiun Spoor : Jurnal Pengabdian Masyarakat, 2025)
The decline in the lives of coastal communities in remote areas of Karawang Regency requires concern from various stakeholders, including universities (in this case, Universitas Singaperbangsa Karawang). Therefore, to educate the next generation to foster concern for coastal communities, a community service team carried out this social service activity. The activity location was Tanjungbaru Hutment, Pasirjaya Village, Cilamaya Kulon Subdistrict, Karawang Regency, on Saturday, 9 March 2024. This activity involved 23 students of Universitas Singaperbangsa Karawang, by implementing an observational socialization method. The impact of this activity on the local community, including the provision of food assistance, was significant. Meanwhile, the benefits obtained by the students are primarily related to educating their caring attitude towards people experiencing poverty in their campus area.